The Effect Of Mechanical Properties Of Polyester Resin In Powdered Basalt Composites On Compression Tests - Marjuni, Teuku; Prastyo, Adi; Ansyori, Anang (Jurnal Rekayasa Teknologi dan sains, 2024)
Indonesia is one of the countries that has the most volcanoes in the world, namely 129 volcanoes that are still active and 500 that are inactive. Volcanic eruptions produce lava which reaches the earth's surface and solidifies to form igneous rock. The igneous rocks that are formed include granite, andesite and basalt. Basalt is a dark colored rock, fine grained, and is an igneous rock. These rocks most often form as extrusive rocks (lava flows). Basalt rock has a composition similar to gabbro rock. Hand lay-up is the simplest method and is an open method of composite fabrication. The manufacturing process using this method is by pouring the resin by hand into woven fibers, particles or sheets, then applying pressure and spreading it evenly using a roller or brush. This process is carried out repeatedly until the desired thickness. In this research, compressive strength tests were carried out with a total number of samples or specimens, namely 24. Compression testing was carried out using the HT-2402 computer universal testing machine. Of the variety of test object specimens that can be dry printed and tested only polyester resin with a content of 20-25%. The compressive strength test with the highest strength was obtained on basalt powder sample code TK.P.2 which had a maximum compressive strength value of 3477 kgf.